Carrier-free organic phosphinate flame-retardant master batch and preparation method thereof
By coating and modifying the organic phosphinate flame retardant, the corrosion problems during the processing process and the uneven dispersion of the carrier-free masterbatches are solved, and better compatibility and mechanical properties are achieved.
Patent Information
- Application Number
- CN202411947309.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-18
AI Technical Summary
The organic phosphinate flame retardant has corrosive screws and mold scale problems during processing, and the preparation of the carrier-free masterbatch requires the adjustment of the hardness of the molded particles to ensure uniform dispersion.
Before preparing the carrier-free masterbatch, the powder flame retardant is coated and modified, and an ester additive, an alkaline coupling agent, a lubricant, a dispersant and a binder are added. The coating reaction is carried out through a stirring and heating by a high-speed mixer to form a crosslinking network structure to improve compatibility and stability.
Through the coating modification treatment, the compatibility of the organic phosphinate flame retardant and the substrate is improved, the corrosion of its weak acidity on the equipment is weakened, and the dispersion and mechanical properties are achieved, avoiding the reduction of material performance by twin screw processing.
Smart Images

Figure BDA0005213988250000071 
Figure BDA0005213988250000081 
Figure BDA0005213988250000082
Abstract
Description
Technical Field
[0001] The invention belongs to the field of organic hypophosphite flame retardants, and particularly relates to a carrier-free organic hypophosphite flame retardant masterbatch with good dispersibility and a preparation method thereof. Background Art
[0002] As a flame retardant with high thermal stability, organic phosphite flame retardant is widely used in engineering plastics and elastomers. However, the direct application of powder has problems such as poor processing environment, uneven mixing of pellets and powder, and stratification during the feeding process. To solve this problem, masterbatch products came into being. Masterbatches with carriers will use nylon carriers, polyester carriers or polyolefin carriers according to the application of different substrates, resulting in the prepared masterbatches not being universal. Moreover, masterbatches with carriers need to be prepared by twin-screw extrusion granulation, and then mixed with the substrate by twin-screw processing again during use. Secondary processing will reduce the mechanical properties of the material.
[0003] Therefore, the development of carrier-free masterbatch has become increasingly popular in recent years. Its use is universal and does not require twin-screw granulation, which will not affect the mechanical properties of the material. However, the preparation of carrier-free masterbatch requires adjusting the hardness of the molded particles to ensure that they will not break during transportation and transport, but at the same time, they should not be too hard, resulting in uneven dispersion during the processing process.
[0004] Although organic phosphinate flame retardants have good thermal stability, their weak acid properties can corrode the screw and cause mold deposits during processing. Summary of the invention
[0005] In order to solve the above technical problems, the present invention first coats and modifies the powder flame retardant before preparing the carrier-free masterbatch, on the one hand to improve its compatibility with other substrates, on the other hand to make certain adjustments to its weak acid properties, alleviate the wear and tear of the equipment caused by its weak acid characteristics, and better maintain the physical properties of the substrate.
[0006] On the one hand, the present invention provides a carrier-free organic phosphinate flame retardant masterbatch, characterized in that the flame retardant masterbatch consists of an organic phosphinate flame retardant, an ester auxiliary agent, an alkaline coupling agent, a lubricant, a dispersant and an adhesive, wherein the mass percentage of the organic phosphinate flame retardant is 90-95%, the mass percentage of the ester auxiliary agent is 0.5-1.5%, the mass percentage of the alkaline coupling agent is 0.5%-2%, the mass percentage of the lubricating dispersant is 0.5-1.5%, and the mass percentage of the adhesive is 2-5%. The preparation of the flame retardant masterbatch comprises the following steps:
[0007] The phosphorus-nitrogen composite flame retardant is stirred at high speed by a high-speed mixer and heated to 70-110 degrees, and an ester auxiliary agent and an alkaline coupling agent are added in sequence by spraying to carry out a coating reaction;
[0008] After the coating reaction is completed and the solvent is evaporated, the flame retardant powder is cooled to below 50 degrees, a lubricating dispersant and an adhesive are added, and the powder is stirred again at high speed by a high-speed mixer and heated to 80-120 degrees, and pressed into a flame retardant masterbatch.
[0009] Preferably, the organic phosphinate flame retardant is selected from one or more mixtures of diethyl aluminum phosphinate, diethyl zinc phosphinate, diethyl calcium phosphinate, phenyl aluminum phosphinate, carboxyethyl phenyl aluminum phosphinate, and diethyl-monoethyl composite aluminum phosphinate.
[0010] Preferably, the ester additive is selected from tetraethyl orthosilicate and butyl titanate additives.
[0011] Preferably, the alkaline coupling agent is selected from alkaline silane coupling agents, such as KH550, KH900, KH602 and the like.
[0012] Preferably, the lubricating dispersant is selected from zinc stearate, calcium stearate, glyceryl stearate, ethylene bisstearamide (EBS), silicone powder, oxidized polyethylene wax or montan wax.
[0013] Preferably, the adhesive is selected from polyester-modified silicone additives, polyester-modified siloxane, pentaerythritol stearate or oleamide.
[0014] Preferably, the ester auxiliary agent is first dispersed in an alcohol solvent, and then a reaction molar equivalent of pure water is added, or directly dispersed in an alcohol-water system, and the reaction is stirred at room temperature until the hydrolysis is completed.
[0015] Preferably, the alkaline coupling agent is first dispersed in an alcohol solvent, and then pure water in a reaction molar equivalent is added, or directly dispersed in an alcohol-water system, and reacted by stirring at room temperature until the hydrolysis is completed.
[0016] The present invention further provides a method for preparing the carrier-free organic phosphinate flame retardant masterbatch as described above, which comprises the following steps:
[0017] The ester additive is first dispersed in an alcohol solvent, and then pure water in a reaction molar equivalent is added, or directly dispersed in an alcohol-water system, and stirred at room temperature until the hydrolysis is completed;
[0018] The alkaline coupling agent is first dispersed in an alcohol solvent, and then pure water in a reaction molar equivalent is added, or directly dispersed in an alcohol-water system, and stirred at room temperature to react until the hydrolysis is completed;
[0019] The phosphorus-nitrogen composite flame retardant is stirred at high speed by a high-speed mixer and heated to 70-110 degrees, and an ester auxiliary agent and an alkaline coupling agent are added in sequence by spraying to carry out a coating reaction;
[0020] After the coating reaction is completed and the solvent is evaporated, the flame retardant powder is cooled to below 50 degrees, a lubricating dispersant and an adhesive are added, and the powder is stirred again at high speed by a high-speed mixer and heated to 80-120 degrees, and pressed into a flame retardant masterbatch.
[0021] The present invention further provides the flame retardant application of the phosphorus-nitrogen composite carrier-free flame retardant masterbatch in a glass fiber reinforced system.
[0022] Preferably, the ratio of the glass fiber reinforcement system is:
[0023] PA6 resin 50-55%, antioxidant 0.4-0.5%, glass fiber 30%, carrier-free flame retardant masterbatch 15%-20%.
[0024] Beneficial effects of the present invention:
[0025] (1) The organic phosphite-compounded melamine polyphosphoric acid system has strong hydrophobicity and is not easy to be well and stably coated by conventional coupling agents. The ester additives first form polyacids after hydrolysis, and then can achieve a multiple cross-linked network structure under high temperature or alkali catalysis. It can be well coated on the surface of the organic phosphite-compounded melamine polyphosphoric acid system, and the formed cross-linked network can achieve better bonding with conventional coupling agents.
[0026] (2) Alkaline coupling agents have many functions. First, alkaline coupling agents can promote the condensation of polyacids formed by ester additives into a macromolecular network structure. Second, the organic phosphite-melamine polyphosphoric acid system has a weak acid property. After being blended with an alkaline coupling agent, the flame retardant system can be made acidic, thereby reducing the corrosion of equipment caused by the flame retardant during processing and application, as well as the mold scale problem caused by the injection molding process. Third, the introduction of organic groups in the alkaline coupling agent can improve the compatibility of the flame retardant component with the substrate, especially the poor compatibility of the acid absorber hydroxides and oxides with the substrate can be significantly improved.
[0027] (3) After double coating, the organic groups of the coupling agent can better combine with the lubricating dispersant and adhesive to achieve good bonding effect of the masterbatch. DETAILED DESCRIPTION
[0028] Example 1
[0029] The ester auxiliary agent used is ethyl orthosilicate, the proportion is 1%, the alkaline coupling agent is KH900, the proportion is 1%, the organic phosphinate is aluminum diethylphosphinate, the proportion is 94%, the dispersing lubricant is oxidized polyethylene wax, the proportion is 1%, and the adhesive is polyester modified siloxane, the proportion is 3%.
[0030] (1) Dispersing and hydrolyzing ethyl orthosilicate in a water-ethanol solution, wherein the molar ratio of ethyl orthosilicate, water, and ethanol is 1:4:10, the reaction is carried out under magnetic stirring at room temperature for 2 hours until the hydrolysis is substantially completed.
[0031] (2) The alkaline coupling agent KH900 was dispersed and hydrolyzed in a water-ethanol solution, with the molar ratio of KH900, water, and ethanol being 1:3:10. The reaction was carried out under magnetic stirring at room temperature for 2 h until the hydrolysis was basically completed.
[0032] (3) Heat and stir diethyl aluminum phosphinate (94%) in a high-speed mixer at a speed of 500 r / min. After the temperature reaches 70 degrees, increase the speed to 1000 r / min, and spray the hydrolyzed ester auxiliary agent solution and alkaline coupling agent solution into the system in sequence. Spray the alkaline coupling agent solution half an hour after the spraying of the ester auxiliary agent solution. After the spraying is completed, react again for half an hour, and adjust the temperature to 110 degrees to evaporate the solvent.
[0033] (4) Cool the powder from the previous step to below 50 degrees, add 1% oxidized polyethylene wax and 3% polyester modified siloxane, quickly stir and disperse evenly, then heat to 90 degrees, discharge the material and convey it to a roller press for extrusion granulation to obtain a carrier-free flame retardant granule product for standby use.
[0034] Example 2
[0035] The ester auxiliary agent used is ethyl orthosilicate, the proportion is 0.8%, the alkaline coupling agent is KH602, the proportion is 1%, the organic phosphinate is aluminum diethylphosphinate, the proportion is 94%, the dispersing lubricant is ethylene bisstearamide (EBS), the proportion is 1.2%, and the adhesive is pentaerythritol stearate, the proportion is 3%.
[0036] (1) Dispersing and hydrolyzing tetraethyl orthosilicate in a water-ethanol solution, wherein the molar ratio of tetraethyl orthosilicate, water, and ethanol is 1:4:8, and reacting with magnetic stirring at room temperature for 2 hours until the hydrolysis is substantially completed.
[0037] (2) The alkaline coupling agent KH602 was dispersed and hydrolyzed in a water-ethanol solution, with the molar ratio of KH602, water, and ethanol being 1:3:8. The reaction was carried out under magnetic stirring at room temperature for 2 h until the hydrolysis was basically completed.
[0038] (3) Heat and stir aluminum diethylphosphinate (94%) in a high-speed mixer at a speed of 500 r / min. After the temperature reaches 80 degrees, increase the speed to 1000 r / min, and spray the hydrolyzed ester auxiliary agent solution and alkaline coupling agent solution into the system in turn. Spray the alkaline coupling agent solution half an hour after the spraying of the ester auxiliary agent solution. After the spraying is completed, react again for half an hour, and adjust the temperature to 110 degrees to evaporate the solvent.
[0039] (4) The powder in the previous step is cooled to below 50 degrees, 1.2% EBS and 3% pentaerythritol stearate are added, and after rapid stirring and dispersion, the temperature is raised to 90 degrees, and the material is discharged and conveyed to a roller press for extrusion granulation to obtain a carrier-free flame retardant granule product for standby use.
[0040] Example 3
[0041] The ester auxiliary agent used is butyl titanate, the proportion is 0.6%, the basic coupling agent is KH602, the proportion is 1%, the organic phosphinate is calcium diethyl phosphinate, the proportion is 95%, the dispersing lubricant is montan wax, the proportion is 0.9%, and the adhesive is pentaerythritol stearate, the proportion is 2.5%.
[0042] (1) Dispersing and hydrolyzing butyl titanate in anhydrous ethanol, the molar ratio of butyl titanate to ethanol is 1:10, reacting under magnetic stirring at room temperature for 1 hour until the dispersion is uniform, and preparing distilled water equivalent to 4 mol of butyl titanate for standby use;
[0043] (2) The alkaline coupling agent KH602 was dispersed and hydrolyzed in a water-ethanol solution, with the molar ratio of KH602, water, and ethanol being 1:3:8. The reaction was carried out under magnetic stirring at room temperature for 2 h until the hydrolysis was basically completed.
[0044] (3) Heat and stir calcium diethylphosphinate (95%) in a high-speed mixer at a speed of 500 r / min. After the temperature reaches 80 degrees, increase the speed to 1000 r / min, and spray the dispersed ester additive, water and alkaline coupling agent solution into the system in sequence. After the dispersed ester additive is sprayed, immediately spray 4 mol of distilled water equivalent to butyl titanate. After stirring for half an hour, spray the alkaline coupling agent solution again. After spraying, react for another half an hour, adjust the temperature to 110 degrees, and evaporate the solvent.
[0045] (4) The powder of the previous step is cooled to below 50 degrees, 0.9% of montan wax and 2.5% of pentaerythritol stearate are added, and after rapid stirring and uniform dispersion, the temperature is raised to 100 degrees, and the material is discharged and conveyed to a roller press for extrusion granulation to obtain a carrier-free flame retardant granule product for standby use.
[0046] Example 4
[0047] The ester auxiliary agent used is ethyl orthosilicate, the proportion is 0.5%, the alkaline coupling agent is KH550, the proportion is 1%, the organic phosphinate is zinc diethylphosphinate, the proportion is 95%, the dispersing lubricant is silicone powder, the proportion is 1%, and the adhesive is pentaerythritol stearate, the proportion is 2.5%.
[0048] (1) Dispersing and hydrolyzing tetraethyl orthosilicate in a water-ethanol solution, wherein the molar ratio of tetraethyl orthosilicate, water, and ethanol is 1:4:8, and reacting with magnetic stirring at room temperature for 2 hours until the hydrolysis is substantially completed.
[0049] (2) The alkaline coupling agent KH550 was dispersed and hydrolyzed in a water-ethanol solution, with the molar ratio of KH550, water, and ethanol being 1:3:8. The reaction was carried out under magnetic stirring at room temperature for 2 h until the hydrolysis was basically completed.
[0050] (3) Heat and stir aluminum diethylphosphinate (95%) in a high-speed mixer at a speed of 500 r / min. After the temperature reaches 80 degrees, increase the speed to 1000 r / min, and spray the hydrolyzed ester auxiliary agent solution and alkaline coupling agent solution into the system in sequence. Spray the alkaline coupling agent solution half an hour after the spraying of the ester auxiliary agent solution. After the spraying is completed, react again for half an hour, and adjust the temperature to 110 degrees to evaporate the solvent.
[0051] (4) Cool the powder from the previous step to below 50 degrees, add 1.2% silicone powder and 3% pentaerythritol stearate, quickly stir and disperse evenly, then heat to 90 degrees, discharge and convey to a roller press for extrusion granulation to obtain a carrier-free flame retardant granule product for standby use.
[0052] Example 5
[0053] The ester auxiliary agent used is butyl titanate, the proportion is 0.8%, the basic coupling agent is KH602, the proportion is 1.2%, the organic phosphinate is aluminum diethylphosphinate, the proportion is 93%, the dispersing lubricant is glyceryl stearate, the proportion is 1%, and the adhesive is pentaerythritol stearate, the proportion is 4%.
[0054] (1) Dispersing and hydrolyzing butyl titanate in anhydrous ethanol, the molar ratio of butyl titanate to ethanol is 1:10, reacting under magnetic stirring at room temperature for 1 hour until the dispersion is uniform, and preparing distilled water equivalent to 4 mol of butyl titanate for standby use;
[0055] (2) The alkaline coupling agent KH602 was dispersed and hydrolyzed in a water-ethanol solution, with the molar ratio of KH602, water, and ethanol being 1:3:8. The reaction was carried out under magnetic stirring at room temperature for 2 h until the hydrolysis was basically completed.
[0056] (3) Heat and stir aluminum diethylphosphinate (95%) in a high-speed mixer at a speed of 500 r / min. After the temperature reaches 80 degrees, increase the speed to 1000 r / min, and spray the dispersed ester additive, water and alkaline coupling agent solution into the system in sequence. After the dispersed ester additive is sprayed, immediately spray distilled water equivalent to 4 mol of butyl titanate. After stirring for half an hour, spray the alkaline coupling agent solution again. After spraying, react for another half an hour, adjust the temperature to 110 degrees, and evaporate the solvent.
[0057] (4) The powder in the previous step is cooled to below 50 degrees, 1% of glyceryl stearate and 4% of pentaerythritol stearate are added, and after rapid stirring and uniform dispersion, the temperature is raised to 90 degrees, and the material is discharged and conveyed to a roller press for extrusion granulation to obtain a carrier-free flame retardant granule product for standby use.
[0058] Comparative Example 1
[0059] Pure powder of aluminum diethylphosphinate 100%, ready for use;
[0060] Comparative Example 2
[0061] No ester auxiliary agent and alkaline coupling agent are used, the organic phosphinate is aluminum diethylphosphinate, the proportion is 95%, the dispersing lubricant is glyceryl stearate, the proportion is 1%, and the adhesive is pentaerythritol stearate, the proportion is 4%.
[0062] (1) At room temperature, aluminum diethylphosphinate (95%), 1% glyceryl stearate and 4% pentaerythritol stearate are added to a high-speed mixer, and after rapid stirring and dispersion, the mixture is heated to 90 degrees, and the mixture is discharged and conveyed to a roller press for extrusion granulation to obtain a carrier-free flame-retardant granule product for standby use.
[0063] Comparative Example 3
[0064] The ester auxiliary agent used is ethyl orthosilicate, the proportion is 1%, the organic phosphinate is aluminum diethylphosphinate, the proportion is 95%, the dispersing lubricant is glyceryl stearate, the proportion is 1%, and the adhesive is pentaerythritol stearate, the proportion is 3%.
[0065] (1) Dispersing and hydrolyzing ethyl orthosilicate in a water-ethanol solution, wherein the molar ratio of ethyl orthosilicate, water, and ethanol is 1:4:10, the reaction is carried out under magnetic stirring at room temperature for 2 hours until the hydrolysis is substantially completed.
[0066] (2) Heat and stir aluminum diethylphosphinate (94%) in a high-speed mixer at a speed of 500 r / min. After the temperature reaches 70 degrees, increase the speed to 1000 r / min, and spray the hydrolyzed ester auxiliary solution into the system. After the ester auxiliary solution is sprayed, react for another half an hour, and adjust the temperature to 110 degrees to evaporate the solvent.
[0067] (4) The powder in the previous step is cooled to below 50 degrees, 1% of glyceryl stearate and 3% of pentaerythritol stearate are added, and after rapid stirring and uniform dispersion, the temperature is raised to 90 degrees, and the material is discharged and conveyed to a roller press for extrusion granulation to obtain a carrier-free flame retardant granule product for standby use.
[0068] Comparative Example 4
[0069] The basic coupling agent used is KH550, the proportion is 1.2%, the organic phosphinate is aluminum diethylphosphinate, the proportion is 95%, the dispersing lubricant is glyceryl stearate, the proportion is 0.8%, and the binder is pentaerythritol stearate, the proportion is 3%.
[0070] (1) The alkaline coupling agent KH550 was dispersed and hydrolyzed in a water-ethanol solution, with the molar ratio of KH550, water, and ethanol being 1:3:10. The reaction was carried out under magnetic stirring at room temperature for 2 h until the hydrolysis was basically completed.
[0071] (3) Heat and stir diethyl aluminum phosphinate (95%) in a high-speed mixer at a speed of 500 r / min. After the temperature reaches 70 degrees, increase the speed to 1000 r / min, spray the alkaline coupling agent solution that has been hydrolyzed into the system, react again for half an hour after spraying, and adjust the temperature to 110 degrees to evaporate the solvent.
[0072] (4) The powder in the previous step is cooled to below 50 degrees, 0.8% of glyceryl stearate and 3% of pentaerythritol stearate are added, and after rapid stirring and uniform dispersion, the temperature is raised to 90 degrees, and the material is discharged and conveyed to a roller press for extrusion granulation to obtain a carrier-free flame retardant granule product for standby use.
[0073] Example 6
[0074] Taking the flame retardant application of PBT glass fiber reinforced system as an example, the products prepared in the above preparation example are added as follows:
[0075] PBT resin 50-55%, antioxidant 0.4-0.5%, glass fiber 30%, carrier-free flame retardant particles 15%-20% in each case, raw materials except glass fiber are mixed in a high-speed mixer and added to the feed port, glass fiber is added through the glass fiber inlet, and the processing temperature of the twin-screw extruder is set to 210-235 degrees. The flame-retardant reinforced modified particles are prepared by strand pelletizing, and after the particles are dried, they are molded by an injection molding machine to prepare various required test strips.
[0076] The physical properties tested in the comprehensive performance table are as follows:
[0077] The test methods for tensile strength and elongation at break of materials are determined in accordance with GB / T1040-2018 Plastics—Determination of tensile properties;
[0078] The material bending strength test method is determined according to GB / T 9341-2008 (three-point bending) standard for the determination of plastic bending properties;
[0079] The material impact strength test method is determined according to GB / T 1843-2008 Plastic Izod Beam Impact Strength Test Standard;
[0080] The material melt index test method is determined according to GB / T3682-2000 Thermoplastic Plastic Melt Mass Flow Rate and Melt Volume Flow Rate Test Standard;
[0081] The vertical combustion test method of the material is determined according to the horizontal and vertical methods of GB / T 2408-2008 Plastics Combustion Performance Determination Standard.
[0082] Table 1 is the processing record of flame retardants of Examples 1-5 and Comparative Examples 1-4;
[0083] Table 2 shows the processing formulas of flame retardant applications of Examples 1-5 and Comparative Examples 1-4, and the serial numbers correspond to the numbers of the above-mentioned preparation examples in sequence;
[0084] Table 3 shows the test results of the flame retardant application of Examples 1-5 and Comparative Examples 1-4, and the serial numbers correspond to the above-mentioned preparation example numbers.
[0085] Table 1
[0086]
[0087]
[0088] Notes: (1) Particle stability After mixing in a high-speed mixer, observe the crushing of the carrier-free masterbatch. (2) The color of the original color plate is light yellow to white, which is a qualified color plate. The gray color is caused by the weak acidity of the product, which leads to the decomposition of the base material. (3) For ultra-thin plates (0.4mm), the dispersion can be observed under light to see if there are white spots of poor dispersion;
[0089] (4) The color of the original color plate is light yellow to white and is a qualified color plate. The gray color plate is caused by the weak acidity of the product, which leads to the decomposition of the base material.
[0090] Table 2
[0091]
[0092] Table 3
[0093]
[0094]
[0095] From the processing record table in Table 1, we can see that compared with the masterbatch prepared by powder, no coating or single-layer coating, the masterbatch prepared by double-layer coating is more stable and the material feeding is smooth. In addition, the dispersion of the flame retardant component is observed by comparison of the formed thin material. The masterbatch prepared by double-layer coating has good compatibility with the substrate, stable processing, and the natural color plate shows a more stable color, which is convenient for color matching of various colors.
[0096] From the comprehensive performance test table in Table 3, it can be concluded that the mechanical properties of flame-retardant glass fiber reinforced materials prepared by processing masterbatch or powder flame retardant are ranked as follows: masterbatch prepared after double-layer coating is the best, alkaline coupling agent coating is better, masterbatch prepared after single-layer coating of ester additives and masterbatch prepared directly without coating have similar performance, and the performance of powder added directly is poor. Because double-layer coating provides better dispersibility and compatibility with the substrate, good mechanical properties are achieved.
Claims
1. A carrier-free organic phosphinate flame retardant masterbatch, characterized in that: The flame retardant masterbatch is composed of an organic phosphinate flame retardant, an ester auxiliary agent, an alkaline coupling agent, a lubricant, a dispersant and an adhesive, wherein the mass percentage of the organic phosphinate flame retardant is 90-95%, the mass percentage of the ester auxiliary agent is 0.5-1.5%, the mass percentage of the alkaline coupling agent is 0.5%-2%, the mass percentage of the lubricating dispersant is 0.5-1.5%, and the mass percentage of the adhesive is 2-5%. The preparation of the flame retardant masterbatch comprises the following steps: The phosphorus-nitrogen composite flame retardant is stirred at high speed by a high-speed mixer and heated to 70-110 degrees, and an ester auxiliary agent and an alkaline coupling agent are added in sequence by spraying to carry out a coating reaction; After the coating reaction is completed and the solvent is evaporated, the flame retardant powder is cooled to below 50 degrees, a lubricating dispersant and an adhesive are added, and the powder is stirred at high speed by a high-speed mixer and heated to 80-120 degrees, and pressed into a flame retardant masterbatch.
2. The carrier-free organic phosphinate flame retardant masterbatch according to claim 1, characterized in that: The organic phosphinate flame retardant is selected from one or more mixtures of diethyl aluminum phosphinate, diethyl zinc phosphinate, diethyl calcium phosphinate, phenyl aluminum phosphinate, carboxyethyl phenyl aluminum phosphinate, and diethyl-monoethyl composite aluminum phosphinate.
3. The carrier-free organic phosphinate flame retardant masterbatch according to claim 1, characterized in that: The ester additive is selected from tetraethyl orthosilicate and butyl titanate additives.
4. The carrier-free organic phosphinate flame retardant masterbatch according to claim 1, characterized in that: The alkaline coupling agent is selected from alkaline silane coupling agents, such as KH550, KH900, KH602 and the like.
5. The carrier-free organic phosphinate flame retardant masterbatch according to claim 1, characterized in that: The lubricating dispersant is selected from zinc stearate, calcium stearate, glyceryl stearate, ethylene bis stearamide (EBS), silicone powder, oxidized polyethylene wax or montan wax.
6. The carrier-free organic phosphinate flame retardant masterbatch according to claim 1, characterized in that: The adhesive is selected from polyester-modified silicone additives, polyester-modified siloxane, pentaerythritol stearate or oleic acid amide.
7. The carrier-free organic phosphinate flame retardant masterbatch according to claim 1, characterized in that: The ester auxiliary agent is first dispersed in an alcohol solvent, and then pure water in a reaction molar equivalent is added, or directly dispersed in an alcohol-water system, and reacted by stirring at room temperature until the hydrolysis is completed.
8. The carrier-free organic phosphinate flame retardant masterbatch according to claim 1, characterized in that: The alkaline coupling agent is first dispersed in an alcohol solvent, and then pure water in a reaction molar equivalent is added, or directly dispersed in an alcohol-water system, and reacted by stirring at room temperature until the hydrolysis is completed.
9. The method for preparing the carrier-free organic phosphinate flame retardant masterbatch according to any one of claims 1 to 8, comprising the following steps: The ester additive is first dispersed in an alcohol solvent, and then pure water in a reaction molar equivalent is added, or directly dispersed in an alcohol-water system, and stirred at room temperature until the hydrolysis is completed; The alkaline coupling agent is first dispersed in an alcohol solvent, and then pure water in a reaction molar equivalent is added, or directly dispersed in an alcohol-water system, and stirred at room temperature to react until the hydrolysis is completed; The phosphorus-nitrogen composite flame retardant is stirred at high speed by a high-speed mixer and heated to 70-110 degrees, and an ester auxiliary agent and an alkaline coupling agent are added in sequence by spraying to carry out a coating reaction; After the coating reaction is completed and the solvent is evaporated, the flame retardant powder is cooled to below 50 degrees, a lubricating dispersant and an adhesive are added, and the powder is stirred at high speed by a high-speed mixer and heated to 80-120 degrees, and pressed into a flame retardant masterbatch.
10. Use of the flame retardant masterbatch of the carrier-free organic phosphinate as claimed in any one of claims 1 to 8 in a glass fiber reinforced system.